ANALISIS STANDAR SARANA PERMUKIMAN DI KELURAHAN LIMBA U II KECAMATAN KOTA SELATAN, KOTA GORONTALO - Faridah, Faridah; Salongi, Asmin; Rauf , Suleman (Program Studi Teknik Arsitektur, Fakultas Teknik, Universitas Ichsan Gorontalo, 2025)
Facilities are one of the important parts in designing settlements. The settlement environment must be provided with facilities such as health facilities, education, worship, government and offices. Good facilities can have a positive influence on people's lives in terms of economy, education, social, culture. This is what prompted us to conduct research on the feasibility of facilities, Limba U II Village, South City District, Gorontalo City. The method used in this study is the data collection method and data analysis method. The analytical descriptive method is used to collect primary and secondary data. The results of the study after analysis based on 8 aspects of facilities identified that there were problems in each aspect, namely the lack of handling, especially in waste processing. Keywords: Analysis; Settlement; Limba U II; Facility Standards.